Disability in the Industrial Revolution Physical impairment in British coalmining, 1780-1880 - Blackie, Daniel (Disability History, 2018)
The Industrial Revolution produced injury, illness and disablement on a large scale and nowhere was this more visible than in coalmining. Disability in the Industrial Revolution sheds new light on the human cost of industrialisation by examining the lives and experiences of those disabled in a sector that was vital to Britain's economic growth. Although it is often assumed that industrialisation led to increasing marginalisation of people with impairments, disabled mineworkers were expected to return to work wherever possible, and new medical services developed to assist in this endeavour. Using a rich and innovative mix of sources ranging from official reports to autobiographies, this book examines disability and its consequences in the coalfields of Scotland, north east England and south Wales. It explores how working conditions, the organisation of labour, and employer attitudes affected the ability of impaired miners to find employment, and charts the multifaceted responses to disablement, ranging from health and safety regulations to welfare programmes. Recognising that experiences of disability extended beyond the world of work, the book discusses the family, community and cultural lives of disabled mineworkers. It shows how disability played an important role in industrial relations and shaped class identity. In the process, it presents a new history of disability and the Industrial Revolution, one that shows how disabled people contributed to Britain's industrial development, and demonstrates how concerns about disability shaped responses to industrialisation.